SISTEM PAKAR DIAGNOSIS PENYAKIT TANAMAN BUAH DALAM POT MENGGUNAKAN METODE DEMPSTER SHAFER BERBASIS WEB - Cahyono, Lulus Okta; Rahmad, Cahya; Affandi, Luqman (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
n recent years there has been a method of planting fruit in pots or often called tabulampot which is very beneficial for cultivators who have limited land. But now the diagnosis of plant diseases using the manual way is to ask directly with an expert.. It is inconvenient a cultivator of plants to make a diagnosis with the constraints of time constraints. Therefore, a system that can diagnose plant-based fruit crop disease, by applying the Dempster Shafer method.The stages of system development used in accordance with the mentioned by kusumadewi, there are 6 stages is the first phase of the state assessment stage which is the process of determining the important things as the basis of the problems analyzed, the second stage is the knowledge collection is the concept of knowledge based search from experts other literature studies. The third stage is the design in which there is the implementation of dempster shafer method using php programming language, the fourth stage is the test phase conducted 3 testing process that is functional testing, testing with excel and the fifth stage accuracy testing is the documentation stage and the last is the maintenance phase.The results of the system in the form of information types of diseases that may attack fruit crops. The results of a trial of 10 cases performed by comparing the suitability of the diagnosis results between the application with the expert, then obtained a percentage or accuracy of 100% truth value of the diagnosis predictions in accordance with the knowledge possessed by the expert.Kata kunci: expert system, tabulampot, dempster shafer